Magnetic field and dilution effects on the slow relaxation of Er3 triangle-based arsenotungstate single-molecule magnets. Issue 35 (7th September 2020) - Chen, Hanhan; Sun, Lin; Zhang, Jinpeng; Xiao, Zikang; Ma, Pengtao; Wang, Jingping; Zhang, Yiquan; Niu, Jingyang
Abstract : Triangular Er3 cluster containing POM exhibits field-induced two thermally activated relaxation processes. Whereas, the diamagnetic dilution sample indicates slow magnetic relaxation with the QTM being partially suppressed. Abstract : A triangular Er3 cluster containing polyoxometalate (POM), [Er3 (μ3 -OH)(H2 O)8 (AsW9 O33 )(AsW10 O35 (dl -mal))]2 22− (1 ) (mal = malate), has been obtained via one-pot reactions. Structural analyses demonstrate that three Er 3+ ions bridged one μ3 -OH to generate a rare μ3 -OH-capped triangular Er3 cluster, which connects two different vacant polyanions to form an unsymmetrical sandwich-type subunit, and adjacent sandwiched subunits are linked through mal ligands to give the targeted dimer. When the Er 3+ ions are substituted in whole or in part with Y 3+ ions, the diamagnetic yttrium analogue [Y3 (μ3 -OH)(H2 O)8 (AsW9 O33 )(AsW10 O35 (dl -mal))]2 22− (2 ) and diluted sample [Er0.15 Y2.85 (μ3 -OH)(H2 O)8 (AsW9 O33 )(AsW10 O35 (dl -mal))]2 22− (Er@2 ) have also been synthesized. Magnetic studies reveal that 1 exhibits field-induced two-step magnetic relaxation processes; the slow relaxation process may arise from intramolecular magnetic interactions, whereas the fast one is likely to originate from the intermolecular dipole–dipole interactions supported by the magnetic results of Er@2 . From ab initio calculations, it is found that although the magnetic anisotropies of 1 mainly originate from individual Er 3+ fragments, the Er 3+ –Er 3+ interactions have a considerable influence on their slow magnetic relaxation processes.